2015
DOI: 10.1111/ajt.13325
|View full text |Cite
|
Sign up to set email alerts
|

Macrochimerism in Intestinal Transplantation: Association With Lower Rejection Rates and Multivisceral Transplants, Without GVHD

Abstract: Blood chimerism has been reported sporadically among visceral transplant recipients, mostly in association with graft-vs-host disease (GVHD). We hypothesized that a higher degree of mixed chimerism would be observed in multivisceral (MVTx) than in isolated intestinal (iITx) and isolated liver transplant (iLTx) recipients, regardless of GVHD. We performed a longitudinal prospective study investigating multilineage blood chimerism with flow cytometry in 5 iITx and 4 MVTx recipients up to one year post-transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 50 publications
8
63
3
Order By: Relevance
“…7,2730 The MDSCs may have an almost entirely recipient-derived origin, as macrochimerism of myeloid cells is hard to detect in intestinal transplantation, 31, 32 which we also confirmed in some of the recipients (data not shown). In this study, we demonstrated that MP expand MDSCs from human bone marrow cells, but not from PBMCs.…”
Section: Discussionsupporting
confidence: 77%
“…7,2730 The MDSCs may have an almost entirely recipient-derived origin, as macrochimerism of myeloid cells is hard to detect in intestinal transplantation, 31, 32 which we also confirmed in some of the recipients (data not shown). In this study, we demonstrated that MP expand MDSCs from human bone marrow cells, but not from PBMCs.…”
Section: Discussionsupporting
confidence: 77%
“…In line with this hypothesis, immunosuppression withdrawal in a liver transplant recipient induced the conversion of mixed to full donor chimerism, despite the lack of GVHD [19]. This case report underscores the role of graft-borne GvH-reactive T cells in neutralizing HvG-reactive T cells and in promoting transplant tolerance [19, 20]. Furthermore, we found in intestinal transplant recipients that expanded intra-graft GVH-reactive T cells may have attenuated the HvG response locally, as high GvH/HvG clonal ratios in the graft were associated with slower replacement of graft T cells by the recipient and less rejection [7].…”
Section: I) Tolerance Mechanisms Associated With Sustained Mixed Chimmentioning
confidence: 70%
“…This has been done previously for investigation of chimerism in peripheral blood after transplantation by our group (28), but previous investigation of chimerism in transplanted intestinal tissue has instead relied on genetic analysis via fluorescent in situ hybridization (FISH), polymerase chain reaction (PCR), or immunohistochemistry (3, 4, 29, 30). Our method allows dynamic and in depth analysis of ILC chimerism and phenotyping.…”
Section: Discussionmentioning
confidence: 99%